Rancangan dan Implementasi Business Intelligence Dashboard Pada Sistem Persediaan Klinik - Wicaksono, Aloysius Ari; Wahjudi, Januar; Prianjaya (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2025)
Medicine supplies are the main thing for various health care services. Analysis of needs for managing medicine supplies in several healthcare service institutions, especially clinics, is still carried out manually. Management of medicine supplies is closely related to the continuity of health services in clinics, where errors in medicine supply management will result in incidents in some clinics of having a shortage of medicine supplies when needed or even excessive medicine supplies, resulting in the medicine expiring before it is sold. To overcome errors in managing medicine supplies, clinics need a system to assist in managing supplies and analyzing medicine needs, thereby minimizing the number of mistakes in purchasing medicines or losses due to medicines not being used until they expire. Business Intelligence Companies often use it to conduct business analysis to help companies make the right decisions according to existing data. Business Intelligence It is also widely used by health care service providers. This research aims to design and implement a Business Intelligence Dashboard system for clinic inventory systems, starting from planning the Data Warehouse, processing Extract Transform Load from the transaction database to the Data Warehouse database, and developing the Business Intelligence Dashboard. The Business Intelligence Dashboard system helps clinic managers procure medicines more accurately, minimizing the occurrence of shortages or excesses of medicine supplies. The research was conducted at the leading XYZ clinic in Jakarta, with several patient visits per month of around 4,000 patients. The results of this research are in the form of a system Business Intelligence Dashboard, which can display information according to the needs of clinic managers and can help manage medicine supplies at the XYZ clinic, including by displaying medicine stock information Fast Moving blanks and the stock distribution pattern of a medicine.